Selenium Yeast Alleviates Dextran Sulfate Sodium-Induced Chronic Colitis in Mice by Reducing Proinflammatory Cytokines and Regulating the Gut Microbiota and Their Metabolites - Wu Z; Li Y; Jiang M; Sang L; Chang B (Dove Medical Press, 2024)
Zeyu Wu,1,* Yan Li,1,* Min Jiang,1 Lixuan Sang,2 Bing Chang1 1Department of Gastroenterology, First Affiliated Hospital of China Medical University, Shenyang, People's Republic of China; 2Department of Gastroenterology, Shengjing Hospital of China Medical University, Shenyang, People's Republic of China*These authors contributed equally to this workCorrespondence: Lixuan Sang, Department of Gastroenterology, Shengjing Hospital of China Medical University, Shenyang, People's Republic of China, Email sanglixuan2008@163.com Bing Chang, Department of Gastroenterology, First Affiliated Hospital of China Medical University, Shenyang, People's Republic of China, Email cb000216@163.comBackground: Inflammatory bowel disease (IBD) is a chronic recurrent gastrointestinal inflammatory disease. Selenium has been reported to have therapeutic potential in IBD. Selenium yeast is a common selenium supplement that is convenient to access. This study explored the effect of selenium yeast on dextran sulfate sodium- (DSS-)induced chronic colitis in mice.Methods: Mice were randomly divided into four groups: the control group, selenium yeast group, chronic colitis group, and chronic colitis+selenium yeast group (n=6). Mice were killed on the 26th day. The disease activity index (DAI) score and histological damage score were calculated. Cytokines, serum selenium, colonic tissue selenium, gut microbiota and their metabolites short-chain fatty acids (SCFAs) were evaluated.Results: Selenium yeast lowered IL-1β, IL-6, TNF-α, IL-17A, IL-22 and IFN-γ (P< 0.05). In addition, selenium yeast significantly elevated Turicibacter, Bifidobacterium, Allobaculum, Prevotella, Halomonas, Adlercreutzia (P< 0.05), and butyric acid (P< 0.05).Conclusion: Selenium yeast could improve DSS-induced chronic colitis in mice by regulating cytokines, gut microbiota and their metabolites.Keywords: selenium yeast, chronic colitis, gut microbiota, metabolism